Control conditions, contamination sources and disifectant agent utilizet in a clean white room - Vargas Valverde, Erick (2017)
A clean white room is a scientifically constructed area to work under aseptic conditions; Is as well as nuclear facilities, microelectronics, food, cosmetic, biosafety, master-formulating pharmacies, cell therapy, metrology facilities, technological research laboratories and pharmaceutical industries use them. Specifically in the pharmaceutical industry, in order to guarantee the conditions in the laboratories where the sterility tests are carried out, the main factors for the control, operation and disinfection of the white rooms must be known, which maintain the concentration of particles in acceptable levels of contamination. Factors such as pressure and internal recirculation of air in the room, coupled with the regulation of temperature, humidity and control of the clothing of the work staff are indispensable for proper operation. Disinfectants based on alcohol, phenol, chlorine, quaternary ammonium, formaldehyde, glutaraldehyde, hydrogen peroxide and peracids are commonly used for the disinfection of walls, floors and work tables. This work contemplates the main factors of control, operation and disinfection of a white room applied in a laboratory of sterility tests in the pharmaceutical industry